2017
DOI: 10.1556/2006.6.2017.054
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid pathological gambling, mental health, and substance use disorders: Health-care services provision by clinician specialty

Abstract: Background and aimsPathological gambling (PG) is an impulse control disorder. This study assessed the burden of co-occurring behavioral addictions and mental health disorders in treatment-seeking patients and estimated the likelihood of receiving care for these disorders by clinician specialty.MethodsStudy data were derived from the Massachusetts All-Payer Claims Database, a representative database, for the period 2009–2013. The sample included commercially insured adult residents of Massachusetts. Univariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In addition, the prevalence rate for co‐occurring psychoactive substance use disorders in combined samples of problem and pathological gambling was estimated at 57.5% . The most prevalent co‐occurring diagnoses among treatment‐seeking patients who had a principal diagnosis of pathological gambling were anxiety disorders (27.8%), episodic mood disorders (25.6%), psychoactive substance use disorders (17.8%), and depressive disorders (13.35) …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prevalence rate for co‐occurring psychoactive substance use disorders in combined samples of problem and pathological gambling was estimated at 57.5% . The most prevalent co‐occurring diagnoses among treatment‐seeking patients who had a principal diagnosis of pathological gambling were anxiety disorders (27.8%), episodic mood disorders (25.6%), psychoactive substance use disorders (17.8%), and depressive disorders (13.35) …”
Section: Introductionmentioning
confidence: 99%
“…A US study demonstrated that patients with a gambling disorder were significantly more likely to receive treatment from social workers or psychologists if their condition was their primary diagnosis, and more likely to receive treatment from the medical sector if they had comorbid psychiatric diagnoses. 34 More remains to be understood about the reasons why a significant proportion of the general populationincluding individuals who screen positive for problem gamblingmay perceive problem gambling as a condition not primarily in need for a professional intervention and assessment, such as in the medical system. For example, this should be seen in the light of a gambling disorder being associated with high rates of psychiatric comorbidity 33 and severe complications including suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our findings are likely to be an incomplete clinical picture of those who participated in the study and of GA members and problem gamblers more generally. Indeed, substance dependence and psychiatric disorders are highly prevalent among problem gamblers (Rodriguez-Monguio, Errea, & Volberg, 2017), and such comorbidities may affect individuals' personal experiences of group therapy treatments, both practically (e.g., in terms of attendance and retention rates) and psychologically (e.g., in terms of factors such as engagement and emotional connectivity). Whether the present results stand up to replication in groups consisting of members with comorbid clinical needs should be a direction of future research.…”
Section: Discussionmentioning
confidence: 99%